2009 2nd Conference on Human System Interactions 2009
DOI: 10.1109/hsi.2009.5091034
|View full text |Cite
|
Sign up to set email alerts
|

Modeling positive experiences in human-computer interaction

Abstract: Transcendence, peak experience, peak performance and flow are some of the most fundamental positive human experiences. This article explores how these experiences could be understood in humancomputer interaction. A mediating concept used in the article is presence, the perceptual illusion of nonmediation in media and human-computer interaction. Positive human experiences are related to presence and implications to modeling positive experiences in humancomputer interaction are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The linkage of players and our built environment through videogames is sustained by the capacity to provide immersive experiences. The illusion of non-mediation between players and content provides a strong sense of presence [52,53]. Studies such as [54,55] have defined that a system is more likely to be immersive depending on in its capacity of graphic representation.…”
Section: Imentioning
confidence: 99%
“…The linkage of players and our built environment through videogames is sustained by the capacity to provide immersive experiences. The illusion of non-mediation between players and content provides a strong sense of presence [52,53]. Studies such as [54,55] have defined that a system is more likely to be immersive depending on in its capacity of graphic representation.…”
Section: Imentioning
confidence: 99%
“…Although the initial motivation for development of the proposed tool came from our own requirements, a quick review of the state of the art revealed that there may be a wider demand for such an instrument because evaluation of human experience is a central problem in many application domains. For instance, user experience research seeks ways and methods for assessing and optimizing subjective factors like perceptions and emotional responses of users during their interactions with products (Hassenzahl and Tractinsky, 2006;Burmester et al, 2010;Saari, 2009;Chamorro-Koc et al, 2009). Research in psychology requires techniques for observation of human experience in concrete situations and settings (e.g., (Rosenhan, 1973;Voss et al, 2013)).…”
Section: Introductionmentioning
confidence: 99%